Targeting ferroptosis: opportunities and challenges of mesenchymal stem cell therapy for type 1 diabetes mellitus - Le Dai; Qing Wang (Stem Cell Research & Therapy)
Abstract Type 1 diabetes mellitus (T1DM) is characterized by progressive β-cell death, leading to β-cell loss and insufficient insulin secretion. Mesenchymal stem cells (MSCs) transplantation is currently one of the most promising methods for β-cell replacement therapy. However, recent studies have shown that ferroptosis is not only one of the key mechanisms of β-cell death, but also one of the reasons for extensive cell death within a short period of time after MSCs transplantation. Ferroptosis is a new type of regulated cell death (RCD) characterized by iron-dependent accumulation of lipid peroxides. Due to the weak antioxidant capacity of β-cells, they are susceptible to cytotoxic stimuli such as oxidative stress (OS), and are therefore susceptible to ferroptosis. Transplanted MSCs are also extremely susceptible to perturbations in their microenvironment, especially OS, which can weaken their antioxidant capacity and induce MSCs death through ferroptosis. In the pathophysiological process of T1DM, a large amount of reactive oxygen species (ROS) are produced, causing OS. Therefore, targeting ferroptosis may be a key way to protect β-cells and improve the therapeutic effect of MSCs transplantation. This review reviews the research related to ferroptosis of β-cells and MSCs, and summarizes the currently developed strategies that help inhibit cell ferroptosis. This study aims to help understand the ferroptosis mechanism of β-cell death and MSCs death after transplantation, emphasize the importance of targeting ferroptosis for protecting β-cells and improving the survival and function of transplanted MSCs, and provide a new research direction for stem cells transplantation therapy of T1DM in the future.